Functional health and symptoms in Spain before and during the COVID-19 pandemic - Jens Lehmann; Bernhard Holzner; Johannes M. Giesinger; Andrew Bottomley; Shaad Ansari; Ludwig von Butler; Georg Kemmler (BMC, 2021)
Abstract Background The impact of the coronavirus disease (COVID-19) pandemic on wellbeing and health has so far been studied using mostly cross-sectional designs. To place recent findings into context, we compared symptoms and functional health status in two independent samples assessed before and during the COVID-19 pandemic. Methods Participants were recruited via an online panel using quota sampling. We assessed symptoms, functional health, and global quality of life with the EORTC QLQ-C30 in two general population samples in Spain (collected in July 2019 and April 2020). We also assessed several COVID-19 related variables, such as adherence to social distancing. Results Data from N = 1010 participants before the pandemic (mean age 47.1 years, 50.5% female) were compared with data from N = 504 participants during the pandemic (mean age 47.1 years, 50.8% female). Participants during the pandemic (vs. before the pandemic) reported lower role functioning and emotional functioning, as well as less symptom burden. A lower degree of social distancing was associated with better functional health and lower symptom burden. Conclusion Our findings indicate an impact of the COVID-19 pandemic on functional health and symptom burden in the Spanish general population. The comparison of before and during the pandemic can be used to benchmark results raised only during the pandemic.